Exploring the nature of social capital to facilitate its inclusion in enterprise education. Issue 8 (4th November 2014) - Harry Matlay, Professor; Bridge, Simon
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the nature of social capital in its applications for enterprise (and entrepreneurship) in order to facilitate its incorporation into the relevant education and training programmes. Design/methodology/approach – Based on examples from the literature and his own experience the author highlights a variety of different uses for social capital in an enterprise context. Findings – This exploration not only confirms social capital's relevance for enterprise but also illustrates and categorises some of the different forms it can take – for instance forms which provide access to relevant information; forms which facilitate trust, mutual obligations and/or credibility; and forms which promote shared norms of behaviour and commitment. Practical implications – Because these different forms can all be crucial but cannot be substituted one for another, they act in the enterprise mix rather like vitamins in a diet. Understanding the variety and uses of social capital is thus important for enterprise and communicating this should form a key part of entrepreneurship education. Originality/value – While some attention is being paid to the relevance of social capital for enterprise, it receives less recognition as a component of the enterprise mix than factors such as financial and human capital – and is rarely included in enterprise education and training programmes. To help educators to correct this omission the paper supplements the theory by suggesting practical examples of the reality of social capital's varied forms and uses.